Autonomic nervous system control of multiple myeloma. (March 2021) - Cheng, Yan; Sun, Fumou; D'Souza, Anita; Dhakal, Binod; Pisano, Michael; Chhabra, Saurabh; Stolley, Melinda; Hari, Parameswaran; Janz, Siegfried
Abstract: The autonomic nervous system (ANS), which consists of antagonistic sympathetic (adrenergic) and parasympathetic (cholinergic) arms, has emerged as an important regulator of neoplastic development, yet little is known about its role in multiple myeloma (MM). Clinical findings that anti-adrenergic β-blocker intake reduces risk of disease-specific death and overall mortality in patients with MM have indicated that adrenergic input may worsen myeloma outcome. However, preclinical studies using β-adrenergic receptor agonists or antagonists produced controversial results as to whether sympathetic pathways promote or inhibit myeloma. Retrospective outcome data demonstrating that high message levels of cholinergic receptor genes predict inferior survival in the Multiple Myeloma Research Foundation CoMMpass trial suggest that parasympathetic input may drive myeloma progression in a subset of patients. Here we review the ill-defined role of the ANS in MM, put myeloma in the context of other cancers, and discuss knowledge gaps that may afford exciting research opportunities going forward.